Putting the President into Presidency: The turbulent situation in Prague and its European repercussions - Tomislav Maršić (Stiftung Wissenschaft und Politik (SWP), 2009)
With the successful vote of no confidence in the Prague lower house against the Civic Democratic (ODS) government, a difficult domestic political constellation has become even more complicated. Although the pro-European Social Democrats (CSSD) have been able to set the tempo since then to a large degree, this has few positive implications for the ratification of the Lisbon Treaty: Not only has this move on the part of the Opposition made the Euroskeptic Czech President the dominant figure of domestic and foreign politics, the political situation in the Senate has also decisively shifted. Here, where the final vote on ratification remains to be taken, an important disciplining factor on the mostly Euroskeptic senators of the majority Civic Democratic Party has been lost since their pragmatic party head is no longer part of the ruling coalition. Independently of these factors, moreover, the upcoming national and European elections will further escalate the already tense and volatile political atmosphere within the country, raising questions about the functionality of the interim government. In sum, these developments mean a dual setback for the EU: first, the new 'government of experts' will scarcely be capable of carrying out the key leadership tasks of the Council Presidency. Second, and more serious: in this situation, the prospects for ratification of the Lisbon Treaty are uncertain at best
Keywords: 320